Hubungan Kompetensi Kepemimpinan Guru PAI dengan Peningkatan Karakter Religius Siswa Kelas VI SDN Lumbung - Kholiq, Abdul; Sa'diyah, Maemunah; Subagiya, Bahrum (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This research discusses the relationship between the leadership competence of Islamic Education teachers and the improvement of students' religious character. The research was conducted at SDN Lumbung. The research problems are the influence of Islamic Education teachers' leadership on students, the improvement of students' religious character, and the relationship between the leadership competence of Islamic Education teachers and the improvement of students' religious character. The purpose of this research is to understand the impact of the leadership competence of Islamic Education teachers on students, the improvement of students' religious character, and the relationship between the leadership competence of Islamic Education teachers and the improvement of students' religious character. The method used is quantitative descriptive, and the data collected is obtained from questionnaires. The research results indicate that the relationship between the leadership competence of Islamic Education teachers and the improvement of students' religious character is 0.702. Furthermore, the results of the analysis show that the correlation test value Sig (0.001) < α (0.05). In addition, the results of the significance test analysis show that Fhitung (56.295) > Ftabel (3.175) with Sig. (0.001) < α (0.05), thus rejecting Ho and accepting Ha.